(untitled) (Bangladesh Journal of Medical Microbiology, 2019)
Dermatophytes are filamentous fungi that cause tiniasis with high prevalence in tropical hot, humid and overcrowded countries like Bangladesh. Antifungal drug resistance among dermatophyte isolates are very common due to irrational and overuse of them. In vitro antifungal susceptibility test may help to select appropriate drug, optimize the therapy and monitor the emergence of drug resistance. This study was undertaken to isolate and identify different dermatophyte species from skin, nail and hair samples and to see the susceptibility pattern of azoles (fluconazole, miconazole and itraconazole) among one of the most common dermatophyte isolates (Trichophyton rubrum) by disk diffusion method. A total of two hundred and forty six patients clinically suspected of dermatophytosis attending in the outpatient department (OPD) of Dermatology and Venereology of BSMMU, Dhaka, were studied from September 2018 to August 2019. All the samples of skin, nail and hair were processed for direct microscopic examination and culture. The species of dermatophytes were identified by gross colony morphology, microscopic features and biochemical tests. Antifungal susceptibility was performed by disk diffusion (Neo-Sensitabs susceptibility testing modified for Dermatophytes) method in Sabouraud’s dextrose agar (SDA) media. Out of 246 specimens 27.2% were positive by microscopy, 28.9% were positive by culture and 26.0% were positive by both microscopy and culture. Tinea cruris (32.4%) was the most prevalent clinical type among all dermatophyte isolates. Among 71 culture positive isolates, T. rubrum (71.8%) was most prevalent followed by T. mentagrophytes (24.0%) and E. floccosum (4.2%). By disk diffusion method fluconazole was found as the most resistant drug (90.2%) against T. rubrum isolates and Itraconazole was the most sensitive (80.4%). Miconazole was found as most intermediate sensitive. Bangladesh J Med Microbiol 2019; 13 (1): 20-23